Peranan Persepsi Dukungan Sosial terhadap Kesejahteraan Subjektif di Sekolah pada Siswa Pondok Pesantren Modern - Hasna Thohiroh; Langgersari Elsari Novianti; Whisnu Yudiana (Psympathic : Jurnal Ilmiah Psikologi, 2019)
Social support is important to predict subjective well-being in school for students, especially support from friends, parents, and teachers. Students who study at Modern Islamic Boarding, they interact with friends and teachers more often than with parents. The purpose of this study to examine the role of perceived social support from friends, parents, and teachers to enhace subjective well-being in school, and also with each dimension of subjective well-being in school, school satisfaction and affect in school. Participants in this study (N = 264) were a junior high school in grades 7 and 8 in one of the Modern Islamic Boarding School in West Java. The data was obtained using a questionnaire. A multiple regression and path analysis were used to analyze the data. The results shows that perceived social support from friends and teacher has positive impact to subjective well-being in school, while perceived social support from parents is not significantly correlated. Futhermore, perceived social support from friends also has a positive role to enhace school satisfaction and affect in school, perceived social support from teacher significantly correlated with school satisfaction but not with affect in school. The limitation of the study and suggestion for future research were discussed.